INVESTIGATING THE IMPACT OF ESTABLISHING AN ACCOUNTING INFORMATION SYSTEM ON ORGANIZATIONAL PERFORMANCE CONSIDERING THE MEDIATING ROLE OF FINANCIAL REPORTING QUALITY - Walaa HosseinAlsaidi; Dr. Sahar Sepasi; Dr. Ali Abdul Hussein Raji Hussain Al Asad (Scholar Express Journals, 2022)
The purpose of this study was to investigate the effect of establishing an accounting information system on organizational performance with respect to the mediating role of financial reporting quality. Descriptive-correlation method was used to conduct this research. The statistical population of the present study included 700 accountants and auditors of companies listed on the Iraqi Stock Exchange, which according to the Cochran's formula, a total of 248 required sample size was determined. A questionnaire with 32 questions was used to examine the research variables. The reliability of the questionnaires was confirmed by Cronbach's alpha coefficient, the content validity of the questionnaires was confirmed by a group of university professors and their construct validity was confirmed by confirmatory factor analysis. Parametric inferential statistical methods such as KolmogorovSmirnov test have been used to ensure the normality of the data and structural equation modeling and path analysis using LISREL software to test the hypotheses. The most important research findings showed that; Establishment of accounting information system has a positive effect on the quality of financial reporting. Establishment of accounting information system has a positive effect on organizational performance. The quality of financial reporting has a positive effect on organizational performance. Establishment of accounting information system through the mediating variable of financial reporting quality has a positive effect on organizational performance
Keywords: Accounting Information System; Organizational Performance; Financial Reporting Quality